2017
DOI: 10.2147/ott.s114714
|View full text |Cite
|
Sign up to set email alerts
|

Rucaparib: the past, present, and future of a newly approved PARP inhibitor for ovarian cancer

Abstract: Rucaparib camsylate (CO-338, AG-014699, PF-01367338) is a potent PARP-1, PARP-2, and PARP-3 inhibitor. Phase I and II studies demonstrated clinical efficacy in both BRCA-mutated (inclusive of germline and somatic) ovarian tumors and ovarian tumors with homologous recombination deficiency (HRD) loss of heterozygosity (LOH). Rucaparib has received the US Food and Drug Administration (FDA) approval for patients with deleterious BRCA mutation (germline and/or somatic)-associated advanced ovarian cancer who have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…[21][22][23] Additionally, Yuen et al 24 reported that the expression of INPP4B was declined in nasopharyngeal cancer cells. 26 In vitro studies revealed that rucaparib induced cytotoxicity might relate to the inhibition of PARP enzyme activity and increase the formation of PARP-DNA complexes, thereby leading to DNA damage and cell apoptosis. 25 These studies apparently explained that the expression level of INPP4B was negatively correlated F I G U R E 5 Effect of rucaparib on cell proliferation and apoptosis in both SaOS2 and U2OS cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Additionally, Yuen et al 24 reported that the expression of INPP4B was declined in nasopharyngeal cancer cells. 26 In vitro studies revealed that rucaparib induced cytotoxicity might relate to the inhibition of PARP enzyme activity and increase the formation of PARP-DNA complexes, thereby leading to DNA damage and cell apoptosis. 25 These studies apparently explained that the expression level of INPP4B was negatively correlated F I G U R E 5 Effect of rucaparib on cell proliferation and apoptosis in both SaOS2 and U2OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rucaparib is one of the PARP inhibitor, which is successfully obtained a license by the Food and Drug Administration and indicated as a new drug for the treatment of patients with advanced ovarian cancer. 26 In vitro studies revealed that rucaparib induced cytotoxicity might relate to the inhibition of PARP enzyme activity and increase the formation of PARP-DNA complexes, thereby leading to DNA damage and cell apoptosis. 27,28 In vivo experiments demonstrated that rucaparib could suppress tumor growth in glioblastoma and small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other adaptation diseases also include breast carcinoma, melanoma, and unspecified solid tumors [ 77 ]. Rucaparib (AG-014669, PF-01367338, trade name: Rubraca, given orally), an FDA granted and recently approved PARP1-based drug for BRCA-mutant ovarian carcinoma patients, is indicated for therapy one line earlier than olaparib [ 78 ]. It has also been investigated against breast, pancreatic, fallopian tube, and peritoneal carcinomas [ 79 ].…”
Section: Parp1 Inhibitors Against Carcinomasmentioning
confidence: 99%
“…It has also been investigated against breast, pancreatic, fallopian tube, and peritoneal carcinomas [ 79 ]. Further investigations have significantly found the tumoricidal effect of rucaparib in human non-BRCA-mutant ovarian cancer for both monotherapy and combination therapy [ 78 , 80 ]. Veliparib (ABT-888), a benzimidazole-4-carboxamide derivative, has been preclinically studied against breast, ovarian, lung, pancreatic, prostate, testicular and colorectal cancers, and other unspecified solid tumors.…”
Section: Parp1 Inhibitors Against Carcinomasmentioning
confidence: 99%
“…Rucaparib was the first approved PARP inhibitor used in the treatment of patients with deleterious BRCA mutation (germline and/or somatic) associated advanced ovarian cancer that have been treated with two or more chemotherapies (Study 42, Clini-calTrials.gov NCT01078662) [67,68]. The safety of rucaparib was evaluated in 377 patients with advanced ovarian cancer [69].…”
Section: Rucaparibmentioning
confidence: 99%